Infill Density Effects on Impact Strength of PLA+ - Sutjiadi, Adrian; Setiawan, Yosua (Cylinder : Jurnal Ilmiah Teknik Mesin, 2025)
3D printing is an additive manufacturing method. In its process, several parameters can be adjusted to achieve the desired printing results. This study examines the effect of infill percentage on the Charpy impact strength of PLA+ materials made using the fused deposition modeling (FDM) method. The specimens used follow the ISO 179-1 type 1 standard without notches and are made with infill variations of 20%, 40%, 60%, 80%, and 100%. Each variation is tested five times using a JB-S300 Charpy impact tester. The absorbed energy is then calculated into the Charpy impact strength (kJ/m²) according to the ISO 179-1 standard. The results show that the impact strength increases with increasing infill, from 10.9 kJ/m² at 20% infill to 30.4 kJ/m² at 100% infill. These results emphasize the effect of infill on energy absorption and the importance of parameter control to improve the consistency of results in FDM printed PLA+ components.